Design, development and analysis of a battery electric vehicle energy storage system - Cheng, Chai Siang (2017)
The significance of Lithium-Ion Battery technology in the electric vehicle industry has been undoubtedly impactful. The massive advantage of the improved energy-to-weight, power-to-weight ratio and the lengthened battery lifespan over the existing Nickel-variants and lead-acid batteries had leapfrogged the electric vehicle to become on par with the combustion engine vehicle in terms of performance and reliability. The lithium-ion battery cell can be charged or discharged but the conversion of energy from the stored chemical energy to useable electrical energy comes with an efficiency rating or energy loss which manifests as heat energy, causing temperature rise in battery cells. Excessive rise in temperature can cause battery explosion or fire. It is therefore critical that the battery pack is safe from such temperature rises. The focus of the thesis was to design, analyse and manufacture the battery pack to the temperature control requirements of the NTU BEV (Battery Electric Vehicle). The thermal packaging design was designed to extract the waste heat arising from the batteries undergoing energy conversion process. The thermal cooling system was broken down into two essential heat flow paths: 1) through cell connectors and 2) through cooling channels. The cooling system evaluation proceeded with the initial one-dimensional heat transfer calculations. This involved basic heat transfer analysis and manual calculations to ensure the pack will be fit for the purpose of powering the BEV. Once results were tabulated and cooling capacity was found to be adequate, the subsequent more detailed thermal simulation using ANSYS CFD and heat transfer FLUENT software was carried out. The heat transfer analysis enabled a more detailed understanding of airflow paths and temperatures within the battery pack. Several performance assumptions were made to analyse for heat dissipation performance of the cooling system. After the simulation confirmed the feasibility of the pack design, the detail CAD and manufacture was carried out. A complete module was made for testing. The physical battery module assembly was then instrumented with a large number of thermistors throughout the pack. An experimental programme was carried out to measure the temperature during discharge and charge process. Data from experimentation confirmed that the temperature inside the battery module at 1C discharge were well within the prescribed range of the cells. With active cooling by centrifugal fans, a uniform temperature was maintained with small differentials (< 5 °C) across the pack while overall battery temperatures continued to increase to a maximum of 30°C at the center of the module. For the current thermal management scheme, a forced convection flow rate of 4-8 m/s at 25°C is desired to keep the maximum cell temperature below 45°C under discharge/charge load of 1C rate. At higher C-rates, further analysis was carried out using extrapolation techniques. They showed that at 3C, a flow rate of 15.5 m/s is needed. This project enabled a deeper understanding of the ability of forced air convection cooling utilised in battery packs for an electric vehicle environment. The requirements of a battery pack are very stringent, therefore the need to understand a wide range of multidisciplinary engineering topics was required to evaluate the battery pack. Keywords: Lithium-ion batteries; Thermal analysis; Energy Storage System; Battery Electric Vehicle